Transmission In E-Registation Program Implementation - Oktafiani Mustaqorina, Nadilla; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research is to describe and analyze Transmission in the Implementation of the E-Registation Program as an Effort to Ease the Registration of Taxpayer Identification Numbers with a case study of the Lamongan Pratama Tax Service office or KPP Pratama Lamongan. The research method is descriptive qualitative method with interview, observation and documentation technique with purposive sampling technique. The results of this study indicate that the communication variable at the point of transmission of socialization has been carried out by KPP Pratama Lamongan through social media managed by KPP Pratama Lamongan but socialization on social media cannot reach all levels of society and at the point of clarity of online registration if the process has been completed. After completion, KPP Pratama Lamongan will send a physical TIN card using a third party, namely an expedition, but there is uncertainty about the time of receiving a physical TIN card or not receiving a TIN due to unclear delivery addresses and many villages in Dilamongan have multiple RTs in their gangs so that couriers have difficulty sending deliveries. package.